PENURUNAN BOD, COD, DAN ZAT WARNA LIMBAH PENCELUPAN DENGAN FITOEKSTRAKSI MENGGUNAKAN KIAMBANG (Salvinia natans) - I G.A. Kunti Sri Panca Dewi; Putu Suarya; Iryanti E. Suprihatin; Wahyu Dwijani S. (Bumi Lestari Journal of Environment, 2016)
This research was conducted to study the potential of the plants ‘useless’ as kiambang(Salvinia natans) which are easy to find, and not as valuable as textile dyeing waste handlingmedia. Treatment technique used is to replace the growth medium with the waste in questionin this case of waste taken in the dyeing industry. The concentration of methylene blueinwaste of  dye, and congo red, before and after treatment, determined by spectrophotometry.Fluid absorbance was measured at a wavelength of 664 nm for methylene blue and 496 nmfor congo red. Long time treatment used is 6, 12, 18, 24, 30, 36, and 48 hours. These resultsindicate that kiambang (Salvinia natans) is useful to lower BOD and COD of waste dyeing,although its ability to reduce the content of the dye congo red and blue methyl insignificant.This may be caused by too concentrated the dyeing waste.